Upaya Meningkatkan Kemampuan Mengajar Mahasiswa Program Studi Pendidikan Islam Anak Usia Dini (PIAUD) Sekolah Tinggi Ilmu Tarbiyah (STIT)- YPI Kerinci Tahun 2019 - Khairi Khairi (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2020)
The teacher is one of the elements in the teaching and learning process that must play an active role and place its position as a professional task in accordance with the demands of society. Therefore, to be able to carry out their duties and responsibilities, teachers need certain conditions that can be classified into administrative requirements, technical requirements, and personality requirements. Teachers are required to have adequate competency qualifications. Broadly speaking, there are three levels of professional qualifications for teachers as educational professionals, namely capable personalities, teachers as innovators, and teachers as developers. In an effort to improve the teaching abilities of STIT YPI Pangkalan Kerinci , microteaching activities as teaching exercises are carried out by students and it is hoped that a good behavior habit will develop in student teacher candidates. Through microteaching, students also learn to master the professional competences ofteachers which include pedagogical, professional, social, and personality competencies.